Criteria Conceived Commutative Hypercomplex Number Systems Direct Sum of Low-Dimensional Systems - Kalinovsky, J. А. (Інститут проблем реєстрації інформації НАН України, 2012)
It is considered the representativeness criteria of commutative hypercomplex number systems di-rect sum of low-dimensional systems. Those allow construct the efficient algorithms for the classification of hypercomplex number systems. Refs: 9 titles.